Street graphics : thirty-one silkscreen prints, based on South African iconography, with reference to certain characteristics of the street poster - Ford, Simon Gerard (Michaelis School of Fine Art, 2023)
An exploration by graphic means of selected South African iconography is the subject of this thesis. I have produced a collection of thirty-one silkscreen prints, which combine elements of the fine print and the street poster. The screen-prints have been mounted on board and presented in a box, accompanied by an illustrated dissertation. During the production of the printer I displayed a number of individual screen-prints, and later complete series, at various public locations (e.g. bus shelters, fences and walls of buildings) on the U.C.T. campus, in order to relate my working process to a direct public response. The whole collection of prints is ultimately envisaged as an exhibition on simple screens in a public place . The imagery in these prints is drawn from magazines and other mass publications, as well as from personal observation. My themes are based on aspects of South African popular culture and have been developed under eight different titles. The first five prints: OBSERVATIONS, can be seen as the visual parallel to a preface. Series One: ARTEFACTS, asserts the associative values of a well-known object when it is taken out of its context. Series Two: PROTOTYPES, links the quest for individuation with identification by means of uniform or dress. Series Three: INTERIORS, depicts environments that represent the concerns of the people who inhabit them. Series Four: MERE FACADES, portrays selected buildings which reveal aspects of the nature of the society they shelter. Series Five: AHEAD OF OUR TIME, focuses on outward appearance as a denominator of identity and on the resulting loss of individuality. Series Six: SUNNY SKIES, is a personal interpretation of some typical South African images (icons). Series Seven: MEMORABILIA, serves as a conclusion to the collection and is a personal homage to Joseph Cornell. This dissertation comprises a discussion of aspects of the practical work, concentrating on some elements of the historical background to my investigation; notes on my graphic methods and their implications; a documentary report on the display of the prints on the U.C.T. campus and an introduction to the prints.